"Behind each beautiful painting is a child longing to be free": Deep visual listening and children's art during times of crisis. Issue 2 (June 2021) - Chávez Leyva, Yolanda
"Deep visual listening and children's art during times of crisis" explores a way to understand children's art created amidst crisis as well as the meanings we can discern from it through the lens of the "Uncaged Art Tornillo Detention Center" exhibit. In 2018, the U.S. government opened a detention center to hold youth who either crossed the border by themselves or were separated from their families through Trump's Zero Tolerance policy. The youth were from Central America and came seeking asylum. Fleeing profound poverty and violence, they came to save their lives. To deter asylum-seekers through a series of cruel policies, the United States detained the youth in militarized camps where they were under constant surveillance. They did not know when or if they would be released and experienced depression and trauma. An art project at the detention center resulted in their creating approximately 400 pieces, of which 30 survived. "Uncaged Art" exhibited these works in 2019. This article answers the question "What can we learn about the children, the anonymous artists who created the works, through visual listening?" Visual listening is a process that involves all our senses. Listening requires conscious action, unlike hearing which is automatic and is one of the first senses we develop while still in our mother's womb. This methodology allows us to engage with children's art in times of crisis more profoundly than simply seeing the artwork. There are two parts to this practice: deep listening and visual listening. Combined, they provide a powerful way to listen to the stories, the histories, the memories, and the emotions embodied by the art and brought to life by our reflections and understanding